Kajian Pengaruh Perubahan Tata Guna Lahan Terhadap Profil Muka Air Sungai Air Hitam Kota Pekanbaru - Vinka Lyona; Manyuk Fauzi; Sigit Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Air Hitam River is one of the river in Pekanbaru which have the function as the main drainage of the Pekanbaru city. In the past, land surrounding the Air Hitam River Basin is dominated by vegetation that can infiltrate rain water, but as the development of the city, the vegetation areas has changed to housing, offices, warehouses and trade. The change of land use will influence hydrology condition and make river flow higher. If the river is not able to accommodate the rain water, it will cause flooding which cause harm to the surrounding community. For this conditions, it is required data and information about the Air Hitam flooding in the watershed. This study uses the integration of Geographic Information Systems (GIS) and hydraulics models in Hec-GeoRAS. This research used existing land use data in 2010, land use plan in 2026, and land use in extreme condition to estimate. The result showed that in period from 2010 to 2026, the vegetation areas has decreased amounted to 56.778 % to 21.641 %. This causes the value of the composite runoff coefficient land greater so the river can’t accommodate the flow occurs. Discharge that exceeds the capacity of the river caused flooding of 4.5 ha by 2010, 322.338 ha by 2026 and 372.645 ha by extreme conditions. Keywords: land use, flood inundation, Hec-GeoRAS